1997
DOI: 10.1542/peds.100.1.e9
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Lymphocytic Choriomeningitis Virus Syndrome: A Disease That Mimics Congenital Toxoplasmosis or Cytomegalovirus Infection

Abstract: Results. Twenty-six infants with serologically confirmed congenital LCM virus infection were identified. Twenty-two infants were products of term gestations, and birth weights ranged from 2384 to 4400 g (median, 3520 g). Ocular abnormalities, macrocephaly, or microcephaly were the most commonly identified neonatal features. Twentyone infants (88%) had chorioretinopathy, 10 (43%) had macrocephaly (head circumference >90th percentile) at birth, and 3 (13%) were microcephalic (head circumference <10th percentile)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 23 publications
(28 reference statements)
1
123
1
Order By: Relevance
“…6 This study reported on a 28-year-old woman with a diagnosis of EV71 infection during pregnancy, whose obstetric ultrasonograms at 25 weeks of gestation revealed mild fetal hydrocephalus, among other abnormalities. An LCM virus infection, a rarely detected congenital infection, was investigated in 1 case series study, 29 in which 26 cases of LCM virus infection were identified. All 26 patients had hydrocephalus, documented by CT or MRI.…”
Section: Congenital Infectionsmentioning
confidence: 99%
“…6 This study reported on a 28-year-old woman with a diagnosis of EV71 infection during pregnancy, whose obstetric ultrasonograms at 25 weeks of gestation revealed mild fetal hydrocephalus, among other abnormalities. An LCM virus infection, a rarely detected congenital infection, was investigated in 1 case series study, 29 in which 26 cases of LCM virus infection were identified. All 26 patients had hydrocephalus, documented by CT or MRI.…”
Section: Congenital Infectionsmentioning
confidence: 99%
“…LCMV infection in a pregnant woman can spread to the fetus, resulting in abortion early in pregnancy (Deibel et al, 1975) or malformations, including hydrocephalus, intracranial calcifications, and chorioretinitis if the infection occurs later in pregnancy (Ackermann et al, 1974;Sheinbergas, 1975;Barton et al, 1993Barton et al, , 1996Wright et al, 1997;Marrie and Saron, 1998;Barton and Hyndman, 2000;Jamieson et al, 2006;Bonthius et al, 2007b). A study by Bonthius and colleagues (2007b) reports on 20 children with serologically confirmed congenital LCMV infection who were followed for up to 11 years.…”
Section: Lcmv Infection In Pregnancymentioning
confidence: 99%
“…Human transmission has been shown to occur in utero, upon transplantation with infected organs or upon contact with infected hamsters or laboratory animals (2)(3)(4). Congenital LCMV infection acts as an abortifacient and a fetal teratogen commonly manifested as chorioretinitis, hydrocephalus and microcephaly or macrocephaly (5)(6)(7)(8)(9). Adult infection with LCMV can lead to the development of fever, malaise, headaches, seizure and in some cases fatal meningitis (3,(10)(11)(12)(13).…”
Section: General Background On Lcmvmentioning
confidence: 99%